2017
DOI: 10.1161/strokeaha.116.015590
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemotactic Protein-1–Interleukin-6–Osteopontin Pathway of Intra-Aneurysmal Tissue Healing

Abstract: Background and Purpose We have previously demonstrated that the local delivery of monocyte chemotactic protein-1 (MCP-1) via a MCP-1-releasing poly(lactic-co-glycolic acid) (PLGA) -coated coil promotes intra-aneurysmal tissue healing. In this study, we demonstrate that interleukin-6 (IL-6) and osteopontin (OPN) are downstream mediators in the MCP-1-mediated aneurysm healing pathway. Methods Murine carotid aneurysms were created in C57BL/6 mice. Drug-releasing coils (MCP-1, IL-6 and OPN) and control PLGA coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…The heatmap confirms the significant positive correlations between increased power and SOD and MDA, but indicates a negative correlation with pro-inflammatory cytokines MIP-1β, MIG, and VEGF. MIP-1β and MIG represent inflammatory chemokines responsible for recruiting immune cells to damaged tissues, playing a role in the healing process (Wood et al, 2014;Hosaka et al, 2017). The elevated SOD and MDA levels in the high power group confirm previous reports indicating that acute aerobic exercise affects antioxidant levels and redox balance (Kawamura and Muraoka, 2018), which can be detected in the blood as it becomes a source of free radical production in erythrocytes and leukocytes (Nikolaidis and Jamurtas, 2009).…”
Section: Cytokines and Oxidative Stress Markers Differentiating Powersupporting
confidence: 80%
“…The heatmap confirms the significant positive correlations between increased power and SOD and MDA, but indicates a negative correlation with pro-inflammatory cytokines MIP-1β, MIG, and VEGF. MIP-1β and MIG represent inflammatory chemokines responsible for recruiting immune cells to damaged tissues, playing a role in the healing process (Wood et al, 2014;Hosaka et al, 2017). The elevated SOD and MDA levels in the high power group confirm previous reports indicating that acute aerobic exercise affects antioxidant levels and redox balance (Kawamura and Muraoka, 2018), which can be detected in the blood as it becomes a source of free radical production in erythrocytes and leukocytes (Nikolaidis and Jamurtas, 2009).…”
Section: Cytokines and Oxidative Stress Markers Differentiating Powersupporting
confidence: 80%
“…We thus postulated that the atrophy-and CeVD-linked OPN is associated with clinical cognitive performance as well, and our study demonstrated for the first time that increased plasma OPN was associated with poor performance in both global as well as all domain-based cognitive functions, thus expanding upon previous findings of OPN correlations with MMSE [33,34]. The observed associations of OPN with all seven domain-based cognitive functions highlights the potential involvement of OPN, either directly or through regulation of neuroinflammation [27,28], in the pathophysiology of cognitive impairment. This postulate is further supported by the data showing plasma OPN associations with elevation of peripheral inflammatory cytokines including IL-6, IL-8 and TNF.…”
Section: Discussionsupporting
confidence: 81%
“…OPN, also known as early T-lymphocyte activation (ETA-1) or secreted phosphoprotein 1 (SPP1), is an extracellular phosphoprotein expressed in various tissues and cells in response to stress and injury. It may be upregulated under hypoxic conditions [20,21], atherosclerosis [22,23], angioplasty [24], cerebral ischemia [25,26], and by pro-inflammatory cytokines such as interleukin-1β and interleukin-6 [27,28]. OPN has in turn been shown to regulate macrophage infiltration and cytokine production [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Ccl2, or monocyte chemoattractant protein-1 (MCP-1), is responsible for the recruitment of macrophages to the site of inflammation (33,34). The release of IL-6 and Ccl2 are closely linked (35), whereby IL-6 induces Ccl2 expression by peripheral blood mononuclear cells (36) while Ccl2 induces the release of IL-6 by human epithelial cells (37). Increasing levels of IL-6 has been demonstrated in response to injurious ventilation in clinical (20) and experimental (17) studies.…”
Section: Discussionmentioning
confidence: 99%